2017
DOI: 10.1177/2309499017716070
|View full text |Cite
|
Sign up to set email alerts
|

Diminished abductor muscular strength in patients with valgus-impacted femoral neck fractures treated by internal fixation: Clinical study and biomechanical considerations

Abstract: Background: Valgus-impacted femoral neck fractures treated with internal fixation occasionally result in unsatisfactory postoperative locomotive function, partially due to muscle shortening and a decrease in the moment arm. This study quantifies the degree of diminished abduction strength both clinically and biomechanically. Methods: Fifteen patients were enrolled in this study. Twelve patients with fracture healed in valgus-impacted position were further evaluated. Muscular strength around hip was examined, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
2
13
0
1
Order By: Relevance
“…7,8 Our previous study also demonstrated that a 15° valgus impaction, using biomechanical computerized bony models, decreases the moment arm of abduction by approximately 10% and that only abduction of hip joint at the operated side was significantly lesser when compared with the healthy contralateral side during clinical examination. 9 This clinical result coincides with the report of Zlowodzki et al 8…”
Section: Introductionsupporting
confidence: 91%
“…7,8 Our previous study also demonstrated that a 15° valgus impaction, using biomechanical computerized bony models, decreases the moment arm of abduction by approximately 10% and that only abduction of hip joint at the operated side was significantly lesser when compared with the healthy contralateral side during clinical examination. 9 This clinical result coincides with the report of Zlowodzki et al 8…”
Section: Introductionsupporting
confidence: 91%
“…We expect that this simple reduction technique will increase the bone contact area by restoring the femoral neck alignment. 2,6) Previous reports suggested that the optimal posi- tioning of screws over a wide area would reduce the risk of nonunion after multiple-screw fixation. 1) Valgus deformity in the femoral neck leads to a decrease in the femoral neck dimension, which reduces the contact area and space for screw insertion.…”
Section: Discussionmentioning
confidence: 99%
“…2,4) A significant decrease in abductor strength was observed in patients with a valgus-healed femoral neck due to a decrease in the moment arm. 6) In addition, many studies verified that a healed valgus-impacted FNF can cause anterior femoroacetabular impingement (FAI) because of a large bump on the anterolateral side of the femoral headneck transition that causes a cam lesion on the femoral neck and leads to progressive hip arthrosis. 5) Steinmann pins (S-pins) are a thin metal rod commonly used in orthopedic procedures to hold large bone fractures together or control the reduction of the fracture.…”
mentioning
confidence: 99%
“…High rate of fracture re-displacement has been found in valgus impacted femoral neck fracture patients with Conservative treatment [4,5,6] . Fracture fixed in situ without anatomical reduction contributed to increasing reports of complications, which would reduce the Harris Hip Score such as femoral neck shortening, inferior offset and femoroacetabular impingement syndrome [3,7,8] . Anatomical reduction and internal fixation has been considered necessary to enhance bony healing and reduce the rate of avascular necrosis and complications.…”
Section: Introductionmentioning
confidence: 99%